Clowning around: stories facts puzzles poems fun! (Shortland Publications Auckland, 2003)
A young girl discovers the joy of clowning as she learns new skills and tricks. Through her journey, she embraces creativity and self-expression. As she gains confidence, she makes new friends and finds happiness in bringing joy to others. The story highlights the importance of laughter and the impact of humor in everyday life.